SAFETY AND EFFECTIVENESS OF LEFT SIDE COLONOSCOPY OR SIGMOIDOSCOPY VERSUS TOTAL COLONOSCOPY IN PATIENTS LESS THAN 45 YEARS OLD AGE PRESENTED WITH THE PERIANAL DISEASE AT KURDISTAN CENTER FOR GASTROENTEROLOGY/ SULAYMANIYAH - Ahmed, Sarko Jamal; Mohamed, Mohamed Abdulrahman; Mohamed, Mohamed Abdulrahman (Journal of Sulaimani Medical College, 2022)
Background Colonoscopy and flexible sigmoidoscopy are recommended tools for diagnosing colorectal diseases, but their relative effectiveness needs to be clarified. Direct comparisons of colonoscopy and sigmoidoscopy in the same population would help inform patients, providers, and policymakers about patients presented with perianal features and colorectal cancer (CRC) screening options. Objectives To evaluate the ability of each of these two modalities (colonoscopy and sigmoidoscopy) to reach the diagnosis in patients presenting with features suggestive of perianal disease and to determine factors that predict safely performing left-sided colonoscopy in patients less than forty-five years old given with features suggestive of perianal disease. Materials and Methods This prospective cross-sectional study will be conducted between the 1st of January 2021 and the 1st of January 2022 in the department of KCGH (Kurdistan center for gastrointestinal and Hepatology) / TeachingHospital, Sulaymaniyah City, Iraq. One thousand patients presented with features (bright red bleeding perrectum, blood on toilet tissue, pain and itching in anal region, anal soiling) of perianal disease were subjected to sigmoidoscopy and extended to full colonoscopy. The patients are divided into two groups, each group of 500 patients. The first group (basic group) includes patients younger than 45 years and the second group (comparison group) includes patients aged equally and more than 45 years. Results The mean age of the primary group is about 33 years. All patients underwent sigmoidoscopy and extended to total colonoscopy with terminal ileal intubation; in the basic group, we have 48 (4.8%) patients with left side polyps (10 large and 38 small polyps) and 16 (1.6%) right side polyps (2 large and 14 small polyps), in this group, we have only 6 (0.6%) patients with left side colonic mass and no cases of right side colonic mass, while in comparison group we have 115 (11.5%) cases with left side colonic polyp (27 large and 88 small polyps) and about 86 (8.6%) cases of right side colonic polyp, regarding detecting mass in this group we have 20 (2.0%) cases of left side colonic mass and 6 (0.6%) cases of right side colonic mass.. Conclusion Colonoscopy and sigmoidoscopy are important tools for investigating patients presenting with perianal features. While both are sensitive to detecting pathology in the left side of the colon, our study concluded that although colonoscopy is the ideal procedure for detecting lesions in the whole colon (proximal & distal to splenic flexure), limited colonoscopy up to splenic flexure can be safely carried out in patients less than 45 years old presented with perianal diseases.
Keywords: Perianal disease; Sigmoidoscopy; Colonoscopy